Optimized Synthesis of Silver Nanoparticles by Factorial Design with Application for the Determination of Melamine in Milk - Bittar, Dayana Borges [UNESP]; Catelani, Tiago Augusto [UNESP]; Nigoghossian, Karina [UNESP]; Barud, Hernane da Silva [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Taylor & Francis Inc, 2017)
A colorimetric method based on silver nanoparticles was developed for the determination of melamine in milk. Silver nanoparticles were synthesized without any stabilizer, using sodium borohydride as the reducing agent. Optimization of the variables for the formation of the nanoparticles was performed by factorial design, resulting in stable colloidal silver nanoparticles with a mean diameter of 14.0. 2.7 nm. Spectrophotometric measurements performed at 475 nm showed a linear range from 0.033 to 1.50 mg L-1 of melamine with limits of detection and quantification of 0.009 and 0.031 mg L-1, respectively. The method provided highly sensitive determination of melamine in milk.
Keywords: Adulteration; colorimetry; melamine; milk; silver nanoparticles